FEMALE ENTREPRENEURS IN THE COVID 19 ERA: A RETURN TO TRADITIONAL ROLES - Nadia Laaraj (Universitas Nusa Cendana, 2022)
During the last two years, the world has experienced an unprecedented health crisis, and in addition to health and social issues, the economy has been severely affected, with all its actors, particularly the VSEs-SMEs created and managed by women. The main objective of this study was to assess the degree of impact of family responsibilities of Moroccan women entrepreneurs on their efficiency in managing their businesses in difficult times following the Covid 19 pandemic. To do this, we used a qualitative approach and interviewed a sample of thirty women entrepreneurs running VSEs-SMEs. Interviews with these women show that because of this crisis, women have finally chosen and sometimes even been forced to return to their traditional roles of taking care of the home and children especially during the period of lockdown, which has lowered their performance and efficiency in saving their businesses from this crisis. Our results can provide empirical support for support structures to adapt their programmes to the real needs of Moroccan women entrepreneurs, including personalised support, more than technical and financial assistance. Keywords: Female Entrepreneurship; Covid 19; Family Responsibilities; VSEs SMEs.